Kinematics and Kinetics of Youth Baseball Catchers and Pitchers - Gretchen Oliver; Keith Lohse; Sarah Gascon (MDPI AG, 2015)
The purpose of this study was to compare the throwing kinematics and kinetics of youth catchers and pitchers. It was hypothesized that catchers and pitchers would exhibit differences throughout the throwing motion. Descriptive statistics were used to investigate kinematics during the four events of throwing: foot contact (FC), maximum shoulder external rotation (MER), ball release (BR) and maximum shoulder internal rotation (MIR). Additionally, kinetics were investigated within phases of the events: Phase 1 (cocking; FC to MER), Phase 2 (acceleration; MER to BR) and Phase 3 (deceleration; BR to MIR). Results revealed significant difference in torso flexion, lateral flexion, pelvis lateral flexion and segment velocities between the catchers and pitchers. Based on data from the current study, it appears that the youth catchers execute their throw as they have been instructed. It is unclear if the throwing mechanics displayed by these youth are efficient for a catcher, thus further investigation is needed to determine long-term injury susceptibility.